Quantitative evaluation of gastrocnemius medialis mass in patients with chronic heart failure by gray-scale ultrasound and shear wave elastography - Yao, Qiyu; Zhang, Yinglun; Wu, Jun; Shu, Hua; Ye, Xinhua; Li, Ao (Frontiers in Cardiovascular Medicine, 2023)
Objective To assess the usefulness of gray-scale ultrasound (US) and shear wave elastography (SWE) in assessing the condition of the skeletal muscles in patients with chronic heart failure (CHF). Methods We prospectively compared 20 patients with clinically diagnosed CHF and a control population of 20 normal volunteers. The gastrocnemius medialis (GM) of each individual in the rest and the contraction position was assessed using gray-scale US and SWE. The quantitative US parameters including the fascicle length (FL), pinnation angle (PA), echo intensity (EI), and Young's modulus of the muscle were measured. Results In the CHF group compared with the control group, in the rest position, there was a significant difference in EI, PA, and FL of the GM (P < 0.001), but no statistically significant difference in Young's modulus values (P > 0.05); however, in the contraction position, all parameters were statistically different between the two groups (P < 0.001). In the different subgroups of the CHF group grouped according to New York Heart Association staging (NYHA) or left ventricular ejection fraction (LVEF), there were no significant differences in ultrasound parameters in the rest position. However, during the contraction of GM, the smaller the FL and Young's modulus, the larger the PA and EI with the increase of NYHA grade or the decrease of LVEF (P < 0.001). Conclusion The gray-scale US and SWE can provide an objective assessment of skeletal muscle status for CHF patients and are expected to be used to guide their early rehabilitation training and improve their prognosis.